Parasite Fauna of the Blackbelly Garter Snake (Thamnophis melanogaster) in Central Mexico - Frida S. Silva-Trejo; Petra Sánchez-Nava; Armando Sunny; Crystian Sadiel Venegas-Barrera; Javier Manjarrez (Diversity)
Vertebrates function as intermediate hosts for the last larval stages of metazoan parasites and as their definitive hosts where sexual reproduction takes place. In this work, the metazoans that parasitize the snake Thamnophis melanogaster in Laguna de Cuitzeo, Michoacán, were identified, and their infection parameters were calculated to determine the factors that determine the presence of the metazoan species found. A total of 24 snakes (20 adults and 4 neonates) were collected, but only the adults affected by parasitic metazoans were detected, accounting for 54.2% of the total sample. One trematode species, one nematode species, and one acanthocephalan species were found inside the snake. The cystacanth Polymorphus brevis (37.5%) and Contracaecum sp. (25%) stand out for their high prevalence. Ochetosoma brevicaecum and the pentastomids of the genus Porocephalus presented a low prevalence. Only O. brevicaecum uses T. melanogaster as a definitive host. The life cycles of the metazoan that parasitizes T. melanogaster suggest that the snake acquires the infection through active transmission by penetration or passive transmission by ingestion.